Faktor-Faktor yang Berhubungan dengan Perilaku Proaktif Perawat dalam Melaksanakan Handover di Ruang Intensive Care Rumah Sakit - Elvi Mardhiah; Syarifah Rauzatul Jannah; Said Usman; Hajjul Kamil; Dewi Marianthi (Journal of Telenursing (JOTING), 2021)
This study aims to determine the factors associated with proactive behavior in the handover process in the intensive care unit of RSUD Aceh. The method used is a cross-sectional study. Data were analyzed using chi-square and logistic regression analysis with the Backward stepwise test. The results showed that 100 out of 124 respondents were in the category of strong proactive behavior. The results of the chi-square test showed that proactive personality (p-value 0.041), self-efficacy (p-value 0.002) and learning orientation (p-value 0.013) had a relationship with nurses' proactive attitude in carrying out handovers. The results of the logistic regression test showed that the most dominant factor related to the proactive behavior of nurses in carrying out handovers was self-efficacy, with a significance value of 0.020 and an odds ratio of 5.419. In conclusion, self-efficacy is the most significant factor related to the proactive behavior of nurses in the handover process in the intensive care unit of the Aceh General Hospital. Keywords: Handover, Nurse, Proactive Behavior, Intensive Care Room